2016
DOI: 10.1002/aenm.201600676
|View full text |Cite
|
Sign up to set email alerts
|

Re‐engineering the Polymer Capacitor, Layer by Layer

Abstract: be achieved at relatively lower fi elds. [ 3 ] However, this would require the design and the synthesis of new dielectric materials with higher relative permittivity and very low dielectric losses. In addition, because the energy density is proportional to E 2 , it would benefi t by charging the capacitor with as high of an electric fi eld as possible.Another approach, then, would be to use materials with higher barrier heights or electrodes with carefully selected work functions to minimize or retard the tunn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…In recent years, enormous attention and research enthusiasm have been devoted to high dielectric (high-k) materials for their wide applications in actuators [1,2], antennas [3], capacitors [4][5][6][7], wave-transparent (or absorbing) devices [8][9][10][11][12][13], and other electronic devices [14][15][16][17][18][19][20][21][22]. Most conventional highk materials are ceramic or ceramic composites, but their applications are seriously restricted by their intrinsic frangibility, high density, poor plasticity, and low breakdown strength.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, enormous attention and research enthusiasm have been devoted to high dielectric (high-k) materials for their wide applications in actuators [1,2], antennas [3], capacitors [4][5][6][7], wave-transparent (or absorbing) devices [8][9][10][11][12][13], and other electronic devices [14][15][16][17][18][19][20][21][22]. Most conventional highk materials are ceramic or ceramic composites, but their applications are seriously restricted by their intrinsic frangibility, high density, poor plasticity, and low breakdown strength.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric capacitors, which store energy electrostatically, are widely used in pulsed power systems and modern electronics due to the high power density. However, the low energy storage density of dielectric capacitors no longer meets the rising demand for compact, low cost and reliable devices, which limits their further applications . The energy in a dielectric capacitor is stored in the form of electric field and the corresponding energy storage density can be expressed by U=italicEdD, where E is the electric field strength and D is the electric displacement within dielectric materials .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Joyce et al. have demonstrated that a proper thin film can act as electron or hole blocking layer in the polymer capacitor under high electric field, and thereby increase the dielectric strength . Considering alumina thin film generally has a very high dielectric strength, it is a challenge issue to further improve the dielectric strength of CaTiO 3 ceramics by introducing the alumina blocking layer between the electrodes and CaTiO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Introducing insulating blocking layers has been reported as an effective approach to further enhance the energy storage density 33,34 . As shown in the inset of Figure 6A, alumina has been sputtered between Ba(Mg 1/3 Nb 2/3 )O 3 ceramics and the electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that the insulating thin films deposited between the conducting electrodes and the dielectric material can work as the electron or hole blocking layers, which successfully increase the dielectric strength in the polymer and glass capacitors 33,34 . Recently, Zhou et al have demonstrated that the dielectric strength in ceramics can also be further increased with the help of amorphous alumina thin films as the blocking layers 13 .…”
Section: Introductionmentioning
confidence: 99%